Keeping Warm and Dry: The Policy Response to the Struggle for Shelter Among Canada's Homeless, 1900-1960 - Bacher, John; Hulchanski, J. (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1987)
During the first six decades of the 20th century, the social security safety net designed to protect Canadians from destitution has seen many holes. Despite the well documented extent of misery, conservative attitudes of prejudice against the poor through these years prevented the development of an effective community response to poverty and substandard housing conditions. This paper examines the evolution of the Canadian welfare state over three periods. It finds that while a social security system of old age pensions, family allowances and unemployment insurance had emerged by the end of the Second World War, its creation was due more to opportunistic political calculations, than a benevolent effort to reduce homelessness.